Phosphorylation of bio-based compounds: the state of the art. Issue 35 (21st September 2015) - Illy, Nicolas; Fache, Maxence; Ménard, Raphaël; Negrell, Claire; Caillol, Sylvain; David, Ghislain
<x xml:space="preserve">Abstract</x> The aim of this review is to present both fundamental and applied research on the phosphorylation of renewable resources, through reactions on naturally occurring functions, and their use in biobased polymer chemistry and applications.